Spatial and Socio-Religious Characteristics of Muhammadiyah Islamic Housing in Malang City - Ghoffar, Abdul; Mustofa, Muhammad Mutammam; Rizki, Nur Sanif Yusuf Habib; Sholehah, Natasya Eka Putri (Sinektika: Jurnal Arsitektur, 2026)
The features of Muhammadiyah Islamic housing in Malang City show the connection between religious beliefs, cultural identity, and urban change. As a key modern Islamic movement, Muhammadiyah influences its members’ living habits through practical, ethical, and functional ideas. This study uses a descriptive qualitative method with a case study in the Karangbesuki Sub-District. It includes in-depth interviews, spatial observation, and document reviews. The findings indicate that Muhammadiyah housing has a simple and practical architectural style. It supports worship and social activities while keeping public and private spaces separate. In comparison to other urban Islamic communities in Malang, Muhammadiyah housing places more importance on logical planning and moral order rather than symbolic or decorative displays of faith. This research helps to understand how religious beliefs can create unique types of homes that combine spirituality, simplicity, and modern city living.